2 1/4 + 3 2/3 = 9/4 + 11/3
To add these fractions, we need to find a common denominator. The least common multiple of 4 and 3 is 12.
9/4 = 27/12
11/3 = 44/12
So, 2 1/4 + 3 2/3 = 27/12 + 44/12
= 71/12
= 5 11/12
Now, we can subtract this result from 6 11/12
6 11/12 - 5 11/12 = 1/12
Therefore, 6 11/12 - (2 1/4 + 3 2/3) = 1/12
Solve 6 11/12−(2 1/4+3 2/3)
.
Do the operation in parentheses first. Show all your steps.
(2 points)
3 answers
make it sound simple
To solve 6 11/12 - (2 1/4 + 3 2/3), first add the fractions inside the parentheses to get 5 11/12. Then subtract this result from 6 11/12 to get 1/12.
Therefore, 6 11/12 - (2 1/4 + 3 2/3) simplifies to 1/12.
Therefore, 6 11/12 - (2 1/4 + 3 2/3) simplifies to 1/12.